Pengaruh Terpaan Konten Media Sosial Homoseksual Terhadap Sikap Pengguna Akun Pseudonim - Aliifah Thohiroh; Ade Fadli Fachrul (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2026)
This research is motivated by the phenomenon of pseudonymous account usage on the social media platform X, which provides partial anonymity. This allows users to keep their identities confidential while freely expressing their activities, thoughts, and socializing with other pseudonymous account users. This partial anonymity creates a space for the homosexual community to emerge without facing pressures related to their identities. As a User-Generated Content (UGC) based social media platform, other users are potentially exposed to homosexual content that may influence their attitudes towards homosexuality. Based on the above description, the research problem formulated is whether exposure to homosexual content influences attitudes towards homosexuality among pseudonymous account users on platform X. The research method used is quantitative, employing simple regression analysis to examine the correlation, with data collected through questionnaires, observations, and documentation. The research findings indicate that exposure to homosexual content has a strong influence on attitudes towards homosexuality among pseudonymous account users, with an influence percentage of 44%. Pseudonymous account users exposed to homosexual content tend to have increasingly positive attitudes towards homosexuality as the duration, frequency, and attention given to the content increase.